Mixed methods research in the movement sciences: Case studies in sport, physical education and dance (Routledge research in sport and exercise science, 2014)
Mixed methods research techniques, combining both quantitative and qualitative elements, have become well established throughout the social, behavioural and natural sciences. This is the first book to focus on the application of mixed methods research in the movement sciences, specifically in sport, physical education and dance. Researchers and practitioners in each of these fields are concerned with the study of habitual behaviour in naturalistic contexts, and of the concurrent and sequential nature of events and states, precisely the kind of work that multi-method research design can help illuminate.